Validation of the IAC Yokohama system for reporting breast fine-needle aspiration cytology categorization of breast lesions in Vindhya region population - Guru, Aayushi; Suresh Kumar Sutrakar; Jatav, Jagannath; Tripathi, Lokesh; Uday Raj Singh; Gupta, Rakesh; Meena, Hariom; Shambhavi Sharma (Asian Journal of Medical Sciences, 2023)
Background: In 2016, International academy of cytology (IAC) has established a standardized approach for reporting breast fine-needle aspiration cytology (FNAC) by categorizing the lesions in five tier system from C1 to C5 to standardize reporting, which will enhance Breast fine-needle aspiration biopsy cytology performance, interpretation, and reporting. Aims and Objectives: The aim of the study was to categorize FNAC cases according to The IAC Yokohama System and evaluate the diagnostic ability of FNAC. Materials and Methods: The current prospective analytical study was carried out in the Department of Pathology, Shyam Shah Medical College, Rewa, Madhya Pradesh, for a period of 15 months from January 2021 to March 2022 (15 months). A total of 100 cases were included in the study based on inclusion criteria. The results were analyzed based on cytological reporting and P value calculated. Results: Among the 100 cases studied highest number of cases were from the age group of 21–30 years with 29% (n=29). The most common breast laterality affected was left with 69% of affected cases. The maximum number of cases, 69% (n=69) of the total, were found to be categorized under the category C2 (benign) which was followed by Category C5 (Malignant) seen in 13% (n=13). About 9% (n=9) of the total cases were categorized as suspicious of malignancy (C4). Atypical Lesion (C3) and Unsatisfactory Lesions (C1) were categorized in 5% (n=5) and 4% (n=4) of the total cases, respectively. Conclusion: FNAC is a minimally invasive, quick, and efficient pre-operative diagnostic tool that can also be used for postoperative breast lump follow-up to prevent recurrences. FNAC using IAC Yokohama system is a rapid and effective method for the primary categorization of palpable breast lumps and provides better clarity to the clinicians in the management of the patient and can reduce unnecessary surgeries.